Ionic Liquid-Based Ultrasound-Assisted Dispersive Liquid-Liquid Microextraction Followed by High-Performance Liquid Chromatography for the Determination of Bisphenol-A in Sediment Samples - Zhang, C.; Wan, X.Y.; Zhou, C.Z.; Li, Y. (Asian Journal of Chemistry, 2013)
An ionic liquid-based ultrasound-assisted dispersive liquid-liquid microextraction (IL-UAE-DLLME) method was developed for extraction of bisphenol-A from sediments. The analyte were determined by high-performance liquid chromatography equipped fluorescence (FLD) and ultraviolet (VWD) detector. The conditions of DLLME were optimized by an interactive orthogonal array design. Both of the extraction recovery (ER) and extraction factor (EF) were set as the responses for variance analysis. The optimum conditions were as follow: 0.9 mL of acetonitrile, 80 μL of ion liquid, 7 mL of water sample, 5.5 of pH, 15 % of salt effect and < 10 s of extraction time.